Management of Bhindi yellow vein mosaic virus disease - M. DATTA GUPTA, ANJU HANDA and (Indian Phytopathology, 2002)
Fourteen cultivars of okra (bhindi) have been screened for resistance to infection by bhindi yellow vein mosaic virus (BYVMV) under field conditions. Parbhani Kranti has been found to be the most promising variety. Besides, Ghana selection has also been found to be highly resistant to the virus. Agronomic practices improved yield of crop to 65-67 q/ha in spring and 56-61 q/ha in kharif season compared to 37.7 q/ha and 27 q/ha in control in respective seasons. Insecticide Carbofuran 3G has been found better than Phorate lOG and should be applied not only at the time of sowing but also within twenty days after sowing. Two applications of both these insecticides are helpful in achieving a significant reduction in disease incidence and consequent improvement in yield.